Impact of Solvent and Their Contaminants on Pd/C Catalyzed Suzuki‐Miyaura Cross‐Coupling Reactions. Issue 6 (11th May 2021) - de Lambert de Boisjan, Alexandre; Allemann, Christophe; Fadini, Luca
Abstract: The aim of this work was to understand if solvent contaminants can interfere in Suzuki 's cross‐coupling reactions and if it can explain the lack of robustness in industrial processes. For this purpose, several parameters were tested on the industrial model reaction between 2‐bromonaphthalene and phenylboronic acid catalyzed by Pd/C. Best results were obtained using THF as solvent. Traces of the precursors of the used solvents, such as 2, 3‐dihydrofurane or maleic anhydride (100–300 ppm related to the solvent) strongly poisoned the reaction, decreasing the conversion significantly. This means that to ensure robust production, solvent quality must be analyzed at the ppm level. Fortunately, addition of triphenylphosphine can circumvent the catalyst poisoning. Abstract :